Spolupráce obcí (teorie a praxe) na území Moravskoslezského kraje - Bečica, Jiří (Univerzita Pardubice, 2010)
On the base of legal possibilities, paper defines possible ways of municipality cooperation in the Czech Republic. Practical part of the papar analyzes and evaluates the specific cooperation among municipalities by using one of the most frequently used forms of municipality cooperation in the Czech Republic – a voluntary association of municipalities. A specific cooperation of municipalities, including its inclusion into the district in which is the voluntary association of municipalities are operating, its name and purpose acording to status are defined on the example of all municipalities in the Moravian-Silesian Region.
Keywords: Moravian-Silesian Region; voluntary association of municipalities; purpose of cooperation; municipality; budget